2018
DOI: 10.1001/amajethics.2018.979
|View full text |Cite
|
Sign up to set email alerts
|

Does Global Goal Setting Matter for Nutrition and Health?

Abstract: The United Nation's Sustainable Development Goals (SDGs) mark an important moment for the world to improve human capital through nutrition and health goal setting. While the Millennium Development Goals contributed to the reduction in the number of undernourished people, the agenda remains unfinished. We are at a crucial crossroads with malnutrition burdens and hunger not decreasing as fast as they should and sometimes increasing. There is a moral imperative to act on the SDGs for nutrition, and health systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These changes in dietary patterns, supported by greater wealth and higher food affordability, are known as nutrition transition (Drewnowski & Popkin, 1997). However, the health and environmental costs seem to be hidden in inexpensive global staple grain and sugar crops, as shown by the increase in the burden of malnutrition (Fanzo, 2018;Tilman & Clark, 2014). A "Western/unhealthy" pattern has been described as having a high intake of refined grains and sweets, meat, and soft drinks (Murakami et al, 2018).…”
Section: Shift Of Global Traditional Dietsmentioning
confidence: 99%
“…These changes in dietary patterns, supported by greater wealth and higher food affordability, are known as nutrition transition (Drewnowski & Popkin, 1997). However, the health and environmental costs seem to be hidden in inexpensive global staple grain and sugar crops, as shown by the increase in the burden of malnutrition (Fanzo, 2018;Tilman & Clark, 2014). A "Western/unhealthy" pattern has been described as having a high intake of refined grains and sweets, meat, and soft drinks (Murakami et al, 2018).…”
Section: Shift Of Global Traditional Dietsmentioning
confidence: 99%
“…Thus, it seems that food consumption instead of having positive impacts on human health, has significant negative impacts on vital pillars. It will not improve if nations and authorities worldwide do not take suitable sustainable actions; the population is growing each year and more and more food will be needed in the future (Aiking & de Boer, 2018;Bhargava, 2019;Fanzo, 2018;HLPE, 2020;Jones et al, 2016;Röös et al, 2015).…”
Section: Prerequisite For a Sustainable Future: Living In A Harmony With The Environmentmentioning
confidence: 99%
“…All of them set targets for sustainable human development; the most notable one is the 2030 Agenda of UN for Sustainable Development. It sets out a long-term global vision for sustainable development; the 17 Sustainable Development Goals (SDGs) are focussed to achieve a prosperous, socially inclusive, stable economic growth and environmentally sustainable future for humanity, young generations, and the whole planet (Fanzo, 2018;Global Sustainable Development Report, 2019;Johnston et al, 2014;Lucas & Wilting, 2018;Meybeck & Gitz, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The reality of Brazilian family farming reflects the characteristics already demonstrated by studies carried out in other international contexts, which indicated that in the regions where family farming predominates, food culture and inheritances related to existing culinary knowledge are much more varied. In regions where large farms predominate producing staple food (soy, corn, wheat and others), the food habits are based on products purchased in supermarkets, because farmers have FAMILY FARMING AND COVID- 19 3 https://doi.org/10.1590/1678-9865202033e200180 already stopped growing the crops they used for their own nutrition [14]. Small rural properties help to maintain the diversity of agricultural products and nutrients worldwide [15].…”
Section: Introductionmentioning
confidence: 99%